Spontaneous transmural perforation in eosinophilic esophagitis: RARE case presentation and role of esophageal stenting. Issue 6 (14th June 2019) - Issa, Danny; Alwatari, Yahya; Smallfield, George B; Shah, Rachit D
Abstract: Eosinophilic esophagitis (EoE) is a rare disease of the esophagus that is characterized by eosinophilic infiltrate within the esophageal mucosa resulting in chronic inflammation and stenosis. It typically presents with symptoms of esophageal dysfunction with dysphagia and food impaction being the most common presenting complaints. Herein we describe a rare case presentation of a young patient with spontaneous esophageal perforation in the setting of undiagnosed EoE. We suggest that the placement of a covered esophageal stent can provide full closure of the perforation and restoration of the integrity of the GI tract without the need for more invasive open repair. The patient had a short recovery time with no reported postoperative complications upon 30 months follow up. We believe that it's important to consider and rule out EoE in patients with a history of dysphagia and esophageal perforation.